Resilience of Islamic and conventional stocks to geopolitical conflict: A GARCH model analysis - Hasyim, Fuad; Qomar, Moh. Nurul; Saleh, Husny Gibreel Musa (Faculty of Business & Economics, Universitas Islam Indonesia, 2024)
Purpose – This study examines the volatility behavior and resilience of conventional and Islamic stock indices in Indonesia during periods of geopolitical uncertainty, focusing on the Israeli–Palestine conflict.Methodology – This study employs the GARCH(1,1) model to examine the volatility dynamics of four major stock indices: the Jakarta Composite Index (JKSE), LQ45, the Indonesia Sharia Stock Index (JKISSI), and the Jakarta Islamic Index (JII). The analysis covers the period from January 1, 2023, to July 31, 2024, enabling an evaluation of market dynamics before, during, and after the conflict on October 7, 2023.Findings – The results show that conventional indices (JKSE and LQ45) exhibit significant volatility persistence, suggesting a higher susceptibility to prolonged instability during geopolitical tensions. Conversely, the Islamic indices (JKISSI and JII) are more responsive to recent market shocks, indicating greater resilience owing to ethical investment principles that avoid high-risk sectors. Furthermore, this study finds that external macroeconomic factors generally do not significantly influence stock market volatility in Indonesia.Implications – This may be due to the predominance of internal factors and local market dynamics over external global shocks, reflecting the Indonesian market’s less integrated nature in the global financial system. These findings offer valuable insights for investors and policymakers in managing risk and optimizing portfolio strategies amid geopolitical stress.Originality – This study contributes to the growing body of literature on the comparative analysis of conventional and Islamic investments in emerging markets.